Road traffic injured patients with severe GCS and organ injury had a poor prognosis: a retrospective cohort study - Kissanet Tesfay; Mulubirhan Assefa; Dawit Zenebe; Mekonnen Gebremicael; Getahun Kebede; Hayelom Gebrekirstos (BMC, 2019)
Abstract Background Ethiopia had an increasing trend of morbidity and mortality due to road traffic injury. Road traffic injured patient's recovery rate is affected by many different factors. Those factors might affect the duration of time to recovery. Therefore studying the median time to recovery and its predictors of road traffic injured patients will be needed to act upon the patient's hospital provided service. Method A retrospective cohort study design was employed. The study population was all admitted road traffic injured patients in Ayder tertiary hospital. We have used the total of all three-year RTI patients' chart from 2015 to 2017 found in the hospital. After excluding incomplete charts for major variables the sample size was 322. Descriptive statistics, life table, Kaplan-Meier, log-rank test and assumptions of the Cox proportional hazard model was applied. Bi and multivariate Cox regression analysis, hazard ratios and associated 95% CI were estimated. Result Male to female RTI patient ratio was 3:1. Of the total 258(80.1%) had been recovered and the median survival time to recovery was 15 days (interquartile range 7-29). From those recovered, 104(40.3%) had been referred from other health facilities. Availability of referral form linkage [adjusted hazard ratio = 1.5, CI (1.1-1.9)], mild and moderate glass coma scale [adjusted hazard ratio = 2.3, CI (1.3-3.9)], conservative management [adjusted hazard ratio = 1.6, CI (1.2-2.1)], and not having organ injury [adjusted hazard ratio = 1.6, CI (1.1-2.3)] were associated with time to recovery in multivariate analysis. Conclusion Median time to recovery of road traffic injured patients was relatively good. Being referred from another health facility, mild and moderate glass coma scale, conservative management and without organ injury was positively associated with time to recovery of road traffic injured patients. We would like to recommend for future prospective studies to determine the time to return to work of road traffic injured patients and quality of life after the injury.